(untitled) (Journal of Asian Development Studies, 2025)
The main objectives of the study were to investigate current pedagogical trends in the Elementary level, analyze how caregiver competence affects students, and identify factors that affect caregiver performance at the elementary level. This survey-based study used both quantitative and qualitative methods (QUAN-qual.), with a sample of 72 teachers and 360 Elementary school children, for a total of 432 individuals. The researchers followed L.R.GAY’s sampling chart when selecting participants. Research tools included questionnaires with three parts: part 1: demographic; part 2: closed-ended; and part 3: open-ended questions from sampled respondents. Additionally, an observation sheet was used to collect data specific to the Elementary class children. To ensure validity & reliability, all research tools underwent pilot testing to assess accuracy through expert opinion, and Cronbach’s alpha was used to assess questionnaire reliability. SPSS-24 statistical software was used for analysis, which included relevant formulas such as frequency and percentage measures and standard deviation.